Thiol/disulphide balance and ischemia modified albumin levels in relapsed brucellosis patients - Aslan, Mehtap Hülya; Karasahin, Omer; İba Yılmaz, Sibel; Kurt, Ali; Baran, Pervin; Koca Biçer, Cemile (The European Research Journal, 2022)
Objectives: In the study, it was aimed to determine the Thiol/Disulphide profile in patients with relapsed brucellosis and the relationship between Ischemia Modified Albumin (IMA) Levels and Thiol/Disulphide profile. Methods: Native thiol, Total thiol, Disulphide, Disulphide/Native thiol, Disulphide/Total thiol, IMA levels were measured in forty patients with relapsed brucellosis and healthy control group by using the newly developed method in this cross-sectional study. Results: There was no statistically significant difference in patients with relapse brucellosis despite the fact that it was lower than total thiol control group (p > 0.05). Disulphide was detected high in patients with brucellosis but no statistically significant difference was found (p > 0.05). Native thiol and total thiol ratios of disulphide were found to be statistically higher in patients with relapsed brucellosis (p < 0.05). In addition, the ratio of native thiol and native thiol to total thiol was statistically lower than the control group (p < 0.05). The levels of IMA were statistically significant in patients with relapsed brucellosis compared to the control group (p